2021
DOI: 10.1155/2021/3563095
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Spontaneous Imbibition Characteristics of the Deep Longmaxi Formation Shales of the Southern Sichuan Basin, China

Abstract: Deep shale gas reservoirs are a significant alternative type of shale gas reservoir in China. The productivity of deep shale gas wells is lower than that of shallow shale, and the imbibition characteristics of deep shale have a significant effect on the retention and backflow of fracturing fluid and the productivity of shale gas wells. In this study, the pore structure characteristics of organic-rich deep shale in the Lower Silurian Longmaxi Formation of Weiyuan-Luzhou play were analyzed by low-temperature nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Shale gas, as a recognized clean energy source, is becoming increasingly crucial in satisfying the growing energy demand. According to the statistics, shale gas production in the United States accounts for more than half of its total natural gas production; meanwhile, shale gas production will reach 500 × 10 8 m 3 by 2030 in China. , Due to the extremely low permeability in shales, large-scale horizontal drilling and hydraulic fracturing, as well as multistage hydraulic stimulation technologies, were realized to improve the development of shale gas reservoirs in the past decades . As the reservoir space and migration channel of shale gas, the pore structure of shale affects not only the reservoir and adsorption capacity of shale gas but also the seepage characteristics of shale gas.…”
Section: Introductionmentioning
confidence: 99%
“…Shale gas, as a recognized clean energy source, is becoming increasingly crucial in satisfying the growing energy demand. According to the statistics, shale gas production in the United States accounts for more than half of its total natural gas production; meanwhile, shale gas production will reach 500 × 10 8 m 3 by 2030 in China. , Due to the extremely low permeability in shales, large-scale horizontal drilling and hydraulic fracturing, as well as multistage hydraulic stimulation technologies, were realized to improve the development of shale gas reservoirs in the past decades . As the reservoir space and migration channel of shale gas, the pore structure of shale affects not only the reservoir and adsorption capacity of shale gas but also the seepage characteristics of shale gas.…”
Section: Introductionmentioning
confidence: 99%
“…The initial imbibition stage of dodecane is shorter and the nonlinear transition stage is longer. This is due to the fact that the SI of dodecane begins to diffuse slowly in the micropores after rapidly penetrating the intermediate-wetting or oil-wetting macropores and microcracks . In contrast, the SI of brine penetrates the micropores of water-wetting before penetrating the macropores .…”
Section: Results and Discussionmentioning
confidence: 99%
“…This is due to the fact that the SI of dodecane begins to diffuse slowly in the micropores after rapidly penetrating the intermediate-wetting or oil-wetting macropores and microcracks. 40 In contrast, the SI of brine penetrates the micropores of water-wetting before penetrating the macropores. 17 It is worth noting that, compared with Figure 4a, the imbibition volume of dodecane in Figure 4b is larger.…”
Section: Characterization Of Spontaneous Imbibition Inmentioning
confidence: 99%
“…Wang et al (2021) established that the vertical bedding direction limits imbibition, positively correlating it with calcite content but not quartz and clay minerals. Chao et al (2021) claimed that higher TOC content weakens the imbibition rate of the deep Longmaxi Formation shale, while inorganic salt solutions, especially potassium chloride solution, inhibit shale imbibition and the inhibition strength increases with salinity. Based on an NMR-based study of the imbibition process, Zhu et al (2023) concluded that micropores have the largest cumulative proportion of water absorption, followed by mesopores, and macropores make up the lowest cumulative proportion.…”
Section: Introductionmentioning
confidence: 99%